KAIDAH MORFOFONEMIK PREFIKS PENG- DALAM BAHASA INDONESIA - Ayufitriani (Universitas Hasanuddin, 2021)
This study aims to reveal the morphophonemic rules of peng prefixes in Indonesian. This research is a type of qualitative research using a morphophonemic approach. The data in this study are words that use the prefix peng- obtained from digital track records. The method used is the listening method followed by observation and note-taking techniques. In the data analysis, the distribution method was used with the Direct Element Sharing technique. The results showed that there were three morphophonemic processes: (1) phoneme changes occurred in the prefix peng- which was nasalized to /pem-/, /peny-/, /pen-/, and /peng-/; (2) the addition of phonemes occurs in the affix peng- which is nasalized to become /penge-/; and (3) the omission of phonemes occurs in the prefix peng- to /pe/, and basic morphemes with initial phonemes /k/, /t/, /s/, /p/.